2013
DOI: 10.1002/gps.3991
|View full text |Cite
|
Sign up to set email alerts
|

Urinary incontinence in people with Alzheimer's disease

Abstract: unanimously agreed as the best motivator to participate. There was a general feeling that the results of research were not clearly communicated back to participants, influencing future participation.There are commonalities with the literature specific to pharmacological studies (e.g. Grill and Karlawish, 2010), both in the positive and negative features of what engaged people to our research findings, even though we are dealing more with the fundamental principles of engagement in research for PWD and their c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 4 publications
0
5
3
Order By: Relevance
“…Successful toileting requires sufficient mobility to reach a toilet and steadiness to stand (Kyle, ), suggesting that severe ADL dependency strongly affected UI. Regarding the relationship between cognitive function and UI, this study, however, found no significant correlation in between, which is inconsistent with the first hypothesis and findings of previous studies (Alcorn et al, ; Offermans et al, ). The reason for the inconsistency might be that although urinary continence requires adequate cognitive ability to recognise a toilet and the ability to communicate to seek help (Ramphal, ), institutionalised older adults with UI were guided properly by care workers for fixed‐time toilet visits.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Successful toileting requires sufficient mobility to reach a toilet and steadiness to stand (Kyle, ), suggesting that severe ADL dependency strongly affected UI. Regarding the relationship between cognitive function and UI, this study, however, found no significant correlation in between, which is inconsistent with the first hypothesis and findings of previous studies (Alcorn et al, ; Offermans et al, ). The reason for the inconsistency might be that although urinary continence requires adequate cognitive ability to recognise a toilet and the ability to communicate to seek help (Ramphal, ), institutionalised older adults with UI were guided properly by care workers for fixed‐time toilet visits.…”
Section: Discussioncontrasting
confidence: 99%
“…Hence, the correlation between UI frequency and cognitive impairment was lower than expected among these older adults with dementia in this study. The present study also found that agitated behaviours and depression had no direct effect on UI, which is inconsistent with the results of previous studies (Alcorn et al, ; Markland et al, ). This difference is likely because the data estimation used in the previous studies was based on bivariate analysis rather than on path analysis.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Similarly, over 9 years of follow-up of 1453 women aged 65 years, dementia was strongly associated with incident UI [risk ratio (RR) 3.0] [22]. Likewise, in a Scottish study, the prevalence of UI increased with decreasing mini-mental state scores and was notably more common in those with impairments of attention and orientation, verbal fluency, agitation, and disinhibition [23]. In a UK General Practitioner database, when compared with those without a dementia diagnosis, dementia was associated with approximately three times the rate of diagnosis of UI.…”
Section: Dementia and Incontinencementioning
confidence: 93%